Geographic distribution of human leishmaniasis and phlebotomine sand flies in the State of Mato Grosso do Sul, Brazil - Herintha Coeto Neitzke-Abreu; Gabriel Barbosa Costa; Milena Nunes da Silva; Edith Palacio; Alexandre da Silva Cardoso; Paulo Silva de Almeida; Manoel Sebastião da Costa Lima-Junior (Parasites & Vectors, 2022)
Abstract Background In the State of Mato Grosso do Sul, Brazil, sand flies and cases of visceral (VL) and cutaneous (CL) leishmaniases have been reported in almost all municipalities. The aim of this study was to analyze the geographic distribution of VL and CL in relation the sand fly species found in the municipalities of Mato Grosso do Sul. Methods We analyzed VL and CL cases from 2001 to 2018 using data from the Notifiable Diseases Information System (SINAN). Data collected since 2003 on the presence of sand fly vectors (proven or suspected) were provided by the State Health Secretariat. Results A total of 3566 and 3030 cases of VL and CL, respectively, were reported from 2001 to 2018. The municipalities with the most reported cases of VL were Campo Grande (2495), Três Lagoas (442), Corumbá (140) and Aquidauana (136); and those for CL were Campo Grande (635) and Bodoquena (197). The following sand fly species with vector potential were found in 59 municipalities (74.7%): Lutzomyia longipalpis, Lutzomyia cruzi, Nyssomyia whitmani, Migonemyia migonei, Nyssomyia neivai, Pintomyia pessoai, Bichromomyia flaviscutellata and Pintomyia fischeri. Sand flies were present in six municipalities where no cases of VL were reported and in two municipalities where no cases of CL were reported. Conclusions Our results indicate that the geographical distribution of VL and CL in Mato Grosso do Sul expanded during the study period, and highlight the presence of sand fly vectors in municipalities where these diseases are currently considered to be non-endemic. Graphical Abstract